EFFICACY AND TOXICITY OF CARBOPLATIN/PACLITAXEL BASED CHEMORADIATION FOR LOCALIZED OESOPHAGEAL CANCER - Qubtia, Maria; Ishaq, Yasir; Munawar, Kiran; Badar, Farhana; Kazmi, Ather Saeed (Journal of Ayub Medical College Abbottabad, 2017)
Background: The management of Oesophageal and Gastroesophageal junction cancers is challenging. Multimodality therapy with carboplatin/paclitaxel based chemoradiation (CRT) and surgery shows improved efficacy. In this study, we wanted to establish the efficacy and safety of CRT for neoadjuvant and radical treatment of localized oesophageal cancer. Methods: Patients with oesophageal cancer, registered between September 2013 and October 2014 were reviewed retrospectively. Toxicity and efficacy analysis in the form of radiological response rate, R0 resection rate, Progression free survival (PFS) and overall survival (OS) was performed on 102 patients who received radical carbo/pacli induction chemotherapy followed by CRT. Impact of Surgery was seen on PFS and OS. Results: Males and females were 71 (51.1%) and 68 (48.9%) respectively, with squamous cell carcinoma being the predominant histology (92%). Majority of patient belonged to T3/4 and N1 stage. Grade III/IV thrombocytopenia, neutropenia, anaemia, febrile neutropenia requiring hospitalisation, non-hematologic toxicities were noted in 13 (12.8%), 18 (17.7%), 18 (17.7%), 1 (1%), 1 (1%), patients respectively. Complete Radiological response, partial response, Stable disease, progressive disease was seen in 6 (5.9%), 51 (50%), 23 (22.5%) 8 (8.7%), respectively. Resection was done in 29 (28.4%). Complete and partial pathological response were seen 19 (65.5%), 10 (34.4%), respectively. PFS at 40 and 80 weeks was 90%, 73%, respectively and OS at 80 weeks was 86%. PFS at 40 and 80 weeks was 100% and 90.5%, respectively with resection, while it was 86% and 65%, without resection (P value 0.015). OS at 40 and 80 weeks was 100% (both) with resection, while it was 96% and 79.5% weeks without resection. (p-value 0.034). Conclusions: Carbo/pacli based CRT is effective with acceptable toxicity profile in treating localised oesophageal cancer as both as Radical CRT and as a part of multimodality therapy. For definitive results, long term follow up and prospective analysis are required. Keywords: Oesophageal neoplasms; Chemoradiotherapy; Survival; Toxicity